Analysis of the Causes of Death in Victims with Severe Concomitant Injury in an Intensive Care Unit of a Multidisciplinary Hospital - A. V. Vlasenko; O. R. Dobrushina; V. N. Yakovlev; A. V., Shabunin; V. G. Alekseyev; D. A. Shestakov; A. K. Doloksaribu (Общая реаниматология)
Objective: to analyze the causes of fatal outcomes in victims with severe concomitant injury (SCI) in an intensive care unit (ICU) of a multidisciplinary hospital. Subjects and methods. The data on 78 victims with SCI (65 men, 13 women) with SCI without the leading severe brain or spinal injury were retrospectivly analyzed. Results. Intrahospital mortality was 17.9%. The dead and surviving victims had an APACHE II score of 18.4±9.8 and 9.2±7.9, respectively (p=0.0008). According to the ISS scale, injury severity was 41±11.8 scores in the dead and 34.8±10.7 scores in the survivors (p=0.07). The APACHE II and ISS scores were of little prognostic use — AUC (the area under the ROC curve) was 0.19 and 0.35, respectively. Gender and the estimated blood loss volume had no statistically significant impact on mortality. In the structure of mortality, 21.4 and 78.6% fell on early (in the first 5 days after injury) and late (on day 12 or later post-injury), respectively. Late mortality was associated with septic complications in 90.9%. To predict the risk of septic complications, we developed a model including the APACHE II condition severity on admission, chest, limb, and pelvis injury severities. The sensitivity and specificity of the obtained criterion were 87.5 and 84.5%, respectively (AUC 0.88). Conclusion. In SCI, mortality at a present-day multidisciplinary hospital remains high, largely due to late mortality associated with pyoseptic complications. Our developed model may be used in the assessment of fatal septic complications for differentiated prophylaxis.